Ingroup biases of forensic experts: perceptions of wrongful convictions versus exonerations - Scherr, Kyle C. (Psychology, crime & law, 2021)
People inherently prefer and highly value ‘similar others’ - an ingroup bias that meaningfully distorts associated interpretations and perceptions. We examined the extent to which forensic experts exhibited ingroup biases that manifested in asymmetrical skepticisms whereby experts perceived their work, and the work of those they closely work alongside (i.e. prosecutors), as associated with more exonerations than wrongful convictions despite base rate data establishing the opposite. After reporting background characteristics, 93 forensic experts reported the frequency in which five factors - mistaken forensic analysis, false confessions, mistaken eyewitness identifications, prosecutorial misconduct, and inadequate legal defense - were associated with wrongful convictions. Analysts also reported the frequency in which four factors - confession by the actual perpetrator, new forensic evidence analysis, new, non-forensic evidence, and, legal defense organizations - were associated with exonerations. The results revealed ingroup biases and asymmetrical perceptions, with moderate to large effect sizes (ds ≥ .57) whereby experts perceived their work, and the work of those they closely work alongside (i.e. prosecutors), as associated with more exonerations than wrongful convictions. We discuss the basic and practical advances of the observed effects and emphasize the importance of adopting measures to minimize the influence of ingroup biases.